(untitled) (LEARNing Landscapes, 2019)
In 2016, the province of British Columbia introduced a redesigned K-6 curriculum. Undergirding this plan is the learning philosophy, the First Peoples Principles of Learning. This paper is written from the perspective of a settler teacher as she engages in self-study research to develop her understanding of the curricular plan. The author describes her emerging self-awareness as opening to a deeper understanding of her Euro-American worldview, cultural narratives that maintain gaps between settler teachers and First Peoples perspectives, and how ongoing self-inquiry is a way to improve as an educator.